Dielectrics and electrical parts containing them

By using metal oxide particles and nonvolatile organic matter in dielectric materials, and controlling particle size and polydispersity index, the problem of unstable dielectric material constants is solved, and the stability and high performance of dielectric materials in a wide range are achieved.

JP7651035B2Active Publication Date: 2025-03-25ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024051457
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-03-28
Filing Date
2024-03-27
Publication Date
2025-03-25
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

In the prior art, voids are prone to dielectric materials, resulting in unstable dielectric constants and it is difficult to achieve stable values ​​in the range of low to high dielectric constants.

Method used

Using dielectric materials containing metal oxide particles and nonvolatile organic compounds, the polydispersibility index of metal oxide particles is controlled between 10% and 40%. By adjusting the particle size and the proportion of organic compounds, the flexible adjustment of the dielectric constant is achieved.

Benefits of technology

The stability of dielectric materials in the low to high dielectric constant range is achieved, which reduces the existence of voids and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651035000002
    Figure 0007651035000002
  • Figure 0007651035000003
    Figure 0007651035000003
  • Figure 0007651035000004
    Figure 0007651035000004
Patent Text Reader

Abstract

To provide dielectric material which can easily and stably achieve a desired dielectric constant selected from a wide range from low to high dielectric constant, and an electric component which includes the dielectric material.SOLUTION: In a first embodiment, a dielectric is provided which includes metal oxide particles and nonvolatile organic material, the polydispersity index of the metal oxide particles is 10% or more and 40% or less. In a second embodiment, a dielectric member is provided which includes the dielectric identical to the dielectric described in the first embodiment and is insulating material for electronic equipment, insulating material for semiconductor elements, insulating material for an interelectrode material for capacitors, or an electromagnetic wave control material for electromagnetic wave control elements. In a third embodiment, an electromagnetic wave control element is provided which includes a dielectric layer made of the dielectric and a metal layer, and in which the dielectric layer is periodically disposed on the metal layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dielectric and an electrical component including the same. [Background technology]

[0002] Dielectrics have been used in a variety of applications, such as insulating materials for electronic devices, interelectrode materials for capacitors, and insulating films for semiconductor elements. In recent years, there has been a demand for miniaturization and weight reduction in various electrical components, and it is therefore desirable to form dielectrics into micro-sized structures with high precision. For example, by making dielectrics function as metamaterials (more specifically, artificial materials that have a periodic structure finer than the wavelength of electromagnetic waves and thus exhibit behaviors with respect to the electromagnetic waves that are not found in natural materials), it has been considered to use the dielectrics in bandpass filters, high-performance lenses, electromagnetic wave reflectors, and the like.

[0003] Known dielectric materials include polymers, ceramics, etc. Among them, various dielectric materials containing metal oxide particles and polymers have been proposed because it is relatively easy to adjust the dielectric constant.

[0004] Patent Document 1 describes a dielectric thin film characterized by containing polymer-coated zinc oxide fine particles consisting of zinc oxide fine particles and a polymer coating layer having an average thickness of 5 to 500 nm formed on the surface of the zinc oxide fine particles.

[0005] Patent Document 2 describes a transparent dielectric film characterized in that highly dielectric fine particles having polymer graft chains formed thereon are arranged two-dimensionally or three-dimensionally via the polymer graft chains, and the highly dielectric fine particles are BaTiO 3 Fine particles, TiO 2 Fine particles and ZrO 2 It is described that the particle may be at least one type selected from the group consisting of fine particles. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-145161 A [Patent Document 2] JP 2016-216691 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, dielectrics containing fine particles as described in Patent Documents 1 and 2 have a problem in that voids are easily generated. The voids hinder the dielectric from having a high dielectric constant (typically, a relative dielectric constant of 3 or more), and may be a cause of leakage current in, for example, electrical components due to structural non-uniformity within the dielectric. In other words, conventional techniques have not provided a dielectric that can easily and stably achieve a desired dielectric constant in a wide range from low to high dielectric constants.

[0008] The present invention has an object to solve the above problems and to provide a dielectric that can easily and stably achieve a desired dielectric constant selected from a wide range from low to high dielectric constant, and an electrical component including the same. [Means for solving the problem]

[0009] This disclosure encompasses the following items. [Item 1] Metal oxide particles and non-volatile organic matter are included, A dielectric material, wherein the metal oxide particles have a polydispersity index of 10% or more and 40% or less. [Item 2] 2. The dielectric according to item 1, wherein the dielectric constant is 1.5 or more and 10,000 or less. [Item 3] 3. The dielectric according to item 1 or 2, wherein the average particle size of the metal oxide particles is 1 nm or more and 10 μm or less. [Item 4] 4. The dielectric according to any one of items 1 to 3, wherein the metal oxide particles contain copper oxide. [Item 5] 5. The dielectric material according to any one of items 1 to 4, wherein the nonvolatile organic material has a relative dielectric constant of 2 or more and 30 or less. [Item 6] 6. A dielectric member comprising the dielectric material according to any one of items 1 to 5, the dielectric member being an insulating material for electronic devices, an insulating material for semiconductor elements, an interelectrode material for capacitors, or an electromagnetic wave control material for electromagnetic wave control elements. [Item 7] An electromagnetic wave control element including a dielectric layer made of the dielectric material according to any one of items 1 to 5 and a metal layer, An electromagnetic wave control element, wherein the dielectric layers are periodically arranged on the metal layer. [Item 8] Further comprising a periodically arranged metal pattern; The dielectric layer is present between the metal layer and the metal pattern. Item 8. An electromagnetic wave control element according to item 7. [Item 9] The area of ​​the metal layer is 100 mm 2 9. The electromagnetic wave control element according to item 7 or 8. [Item 10] 10. The electromagnetic wave control element according to any one of items 7 to 9, wherein the operating frequency is 0.7 GHz or more and 400 THz or less. [Item 11] Item 11. The electromagnetic wave control element according to item 10, which is an electromagnetic wave reflecting element having a reflection angle of 3° to 70° with respect to an electromagnetic wave incident at 0°. [Item 12] 12. An electromagnetic wave transmitting / receiving system comprising: an electromagnetic wave control element according to any one of items 7 to 11; and an electromagnetic wave transmitting antenna. [Item 13] A method for producing an electromagnetic wave control element including a dielectric layer made of the dielectric material according to any one of items 1 to 5 and a metal layer, A method comprising printing a dielectric onto a metal layer to form said dielectric layer. [Item 14] The electromagnetic wave control element further includes a metal pattern, Item 14. The method of item 13, further comprising exposing the dielectric layer to energy radiation to form the metal pattern. [Item 15] 15. The method according to item 14, wherein the energy irradiation is light irradiation. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a dielectric that can simply and stably achieve a desired dielectric constant selected from a wide range from a low dielectric constant to a high dielectric constant, and an electrical component including the same. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a diagram illustrating a laminate produced in Example 1. [Diagram 2] FIG. 2 is a diagram illustrating a metal pattern in the laminate produced in Example 1. [Diagram 3] FIG. 1 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 1. [Figure 4] 4 is a diagram illustrating a metal pattern in an electromagnetic wave control element manufactured based on the results shown in FIG. [Diagram 5] 5 is a diagram showing a calculation result of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element shown in FIG. [Figure 6] FIG. 1 is a diagram showing a phase calculation result at a frequency of 0.1 THz in the laminate produced in Example 1. [Figure 7] 7 is a diagram illustrating a metal pattern in an electromagnetic wave control element manufactured based on the results shown in FIG. 6. FIG. [Figure 8] 8 is a diagram showing a calculation result of the angular distribution of the reflected wave intensity at a frequency of 0.1 THz in the electromagnetic wave control element shown in FIG. 7. [Figure 9] FIG. 1 is a diagram showing a phase calculation result at a frequency of 8.5 GHz in the laminate produced in Example 1. [Figure 10] 10 is a diagram illustrating a metal pattern in an electromagnetic wave control element manufactured based on the results shown in FIG. [Figure 11]11 is a diagram showing a calculation result of the angular distribution of the reflected wave intensity at a frequency of 8.5 GHz in the electromagnetic wave control element shown in FIG. [Figure 12] FIG. 13 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 2. [Figure 13] FIG. 11 is a diagram showing the calculation results of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element produced in Example 2. [Figure 14] FIG. 13 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 4. [Figure 15] FIG. 13 is a diagram showing the calculation results of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element produced in Example 4. [Figure 16] FIG. 13 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 5. [Figure 17] FIG. 13 is a diagram showing the calculation results of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element produced in Example 5. [Figure 18] FIG. 13 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 7. [Figure 19] FIG. 13 is a diagram showing the calculation results of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element produced in Example 7. [Figure 20] FIG. 13 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 8. [Figure 21] FIG. 13 is a diagram showing the calculation results of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element produced in Example 8. [Figure 22] FIG. 13 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 9. [Diagram 23] FIG. 13 is a diagram showing the calculation results of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element produced in Example 9. [Figure 24] FIG. 13 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 10. [Diagram 25] FIG. 13 is a diagram showing the calculation results of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element produced in Example 10. [Figure 26] FIG. 13 is a diagram showing the phase calculation results at a frequency of 0.5 THz in the laminate produced in Example 11. [Figure 27] FIG. 13 is a diagram showing the calculation results of the angular distribution of the reflected wave intensity at a frequency of 0.5 THz in the electromagnetic wave control element produced in Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, exemplary embodiments of the present invention (sometimes referred to as the present embodiment) will be described, but the present invention is not limited to these embodiments.

[0013] <Dielectric> One aspect of the present invention provides a dielectric material comprising metal oxide particles and a non-volatile organic material. In one aspect, the polydispersity index of the metal oxide particles is 10% or more and 40% or less. The dielectric constant may be evaluated using the relative dielectric constant as an index. According to the dielectric material of this embodiment, such metal oxide particles and a non-volatile organic material are used, and the dielectric constant can be selected as desired from a wide range from low to high dielectric constants by appropriately selecting the types and amounts of the metal oxide particles, the non-volatile organic material, and any additional components. Major factors for increasing or decreasing the dielectric constant of the dielectric material include the average particle size and polydispersity of the metal oxide particles, the dielectric constants of the metal oxide and the non-volatile organic material (specifically, the substance types of these materials), the ratio of the metal oxide particles to the non-volatile organic material, and the amount of voids in the dielectric material. By adjusting these, the desired dielectric constant can be easily and stably achieved. In one aspect, the amount of voids in the dielectric material may be reduced by changing the average particle size and / or polydispersity index of the metal oxide particles.

[0014] [Metal oxide particles] The metal oxide constituting the metal oxide particles includes one or more metal oxides selected from silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium. The metal oxide may be an oxide containing two or more metals (e.g., barium titanate, etc.). From the viewpoint of the stability of the metal oxide and the ease of selecting a combination of the metal species contained in the dielectric and the metal species contained in the metal layer that can be in contact with the dielectric in the electric component according to the desired characteristics of the electric component (for example, the electromagnetic wave reflection characteristics in an electromagnetic wave reflector application), silver, copper, gold, platinum, aluminum, nickel, and iron are preferred, silver, copper, and aluminum are more preferred, and copper is even more preferred. Thus, in a preferred embodiment, the metal oxide particles contain copper oxide.

[0015] The relative dielectric constant of the metal oxide constituting the metal oxide particles is preferably 1.5 or more, or 2 or more, or 2.5 or more, or 5 or more from the viewpoint of increasing the dielectric constant of the dielectric, and is preferably 100 or less, or 50 or less, or 30 or less, or 20 or less from the viewpoint of reducing energy loss of electromagnetic waves in, for example, electromagnetic wave control applications. When two or more types of metal oxides are used, the above relative dielectric constant refers to the value of each metal oxide. Throughout this disclosure, the preferred value of the relative dielectric constant means that the relative dielectric constant measured at any one frequency selected from the range of 1 kHz to 3 THz may be that value.

[0016] In one embodiment, the average particle size of the metal oxide particles is 1 nm or more and 10 μm or less. The average particle size may be selected according to the desired dielectric constant of the dielectric. From the viewpoint of stability against oxidation in air, the average particle size is preferably 1 nm or more, or 5 nm or more, or 10 nm or more, and from the viewpoint that the dielectric is unlikely to become non-uniform and the desired dielectric constant can be stably maintained by reducing the voids in the dielectric, the average particle size is preferably 10 μm or less, or 1 μm or less, or 100 nm or less. When the material and content of the metal oxide particles in the dielectric are the same, if the average particle size of the metal oxide particles is increased, the voids in the dielectric tend to increase, thereby decreasing the dielectric constant of the dielectric. Therefore, for example, in applications requiring a high dielectric constant, it may be advantageous to make the average particle size relatively small, for example, 100 nm or less. In the present disclosure, the average particle size is a value measured by the cumulant method.

[0017] The average particle size of the metal oxide particles can be controlled by adjusting the manufacturing conditions of the metal oxide particles. For example, the average particle size of the silver oxide particles can be controlled by the method described in the patent literature (e.g., JP 2003-308730 A), the average particle size of the aluminum oxide particles can be controlled by the method described in the patent literature (e.g., JP 2001-199718 A), and the average particle size of the cuprous oxide particles can be controlled by adjusting the reduction temperature in the manufacturing method of the cuprous oxide particles as follows.

[0018] In one embodiment, the cuprous oxide particles can be produced by a method of reducing a copper salt dissolved in an aqueous solution with hydrazine. As the copper salt, a divalent copper salt can be suitably used, and examples thereof include copper(II) acetate, copper(II) nitrate, copper(II) carbonate, copper(II) chloride, and copper(II) sulfate. The amount of hydrazine used is preferably 0.2 mol to 2 mol, and more preferably 0.25 mol to 1.5 mol, per mol of the copper salt.

[0019] A water-soluble organic substance may be added to the aqueous solution in which the copper salt is dissolved. By adding the water-soluble organic substance to the aqueous solution, the melting point of the aqueous solution is lowered, so that reduction can be carried out at a lower temperature. As the water-soluble organic substance, for example, alcohol, water-soluble polymer, etc. can be used.

[0020] Examples of alcohol include: Monohydric alcohols such as methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, t-butanol, n-pentanol, i-pentanol, sec-pentanol, t-pentanol, 2-methylbutanol, 2-ethylbutanol, 3-methoxybutanol, n-hexanol, sec-hexanol, 2-methylpentanol, sec-heptanol, 3-heptanol, n-octanol, sec-octanol, 2-ethylhexanol, n-nonyl alcohol, 2,6-dimethyl-4-heptanol, n-decanol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, phenol, benzyl alcohol, and diacetone alcohol; glycols such as ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2-pentanediol, 2-methylpentane-2,4-diol, 2,5-hexanediol, 2,4-heptanediol, 2-ethylhexane-1,3-diol, diethylene glycol, dipropylene glycol, hexanediol, octanediol, triethylene glycol, tri-1,2-propylene glycol, etc.; polyhydric alcohols such as glycerin, etc.; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol tertiary butyl ether, and dipropylene glycol monomethyl ether; Glycol esters such as propylene glycol monomethyl ether acetate; etc. As the water-soluble polymer, for example, polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol copolymer, etc. can be used.

[0021] The temperature during reduction can be, for example, -20°C to 60°C, and is preferably -10°C to 30°C. The average particle size may be adjusted to a desired range by adjusting the reduction temperature. The reduction temperature may be constant during the reaction, or may be increased or decreased during the reaction. In the early stage of the reaction when the activity of hydrazine is high, reduction is preferably performed at 10°C or less, and more preferably at 0°C or less. The reduction time is preferably 30 minutes to 300 minutes, and more preferably 90 minutes to 200 minutes. The atmosphere during reduction is preferably an inert atmosphere such as nitrogen or argon.

[0022] The reaction liquid is then centrifuged to separate the supernatant and the precipitate, and the copper oxide particles are collected as the precipitate.

[0023] The polydispersity index of the particle diameter of the metal oxide particles is, in one embodiment, 10% or more and 40% or less. A high polydispersity index of the particle diameter means a large variation in particle diameter. Such particles are easily packed densely due to the stone wall effect, and contribute to reducing voids in the dielectric and thereby homogenizing the dielectric, and are therefore advantageous in terms of easily and stably obtaining a dielectric having a desired dielectric constant selected from a wide range from a low dielectric constant (in one embodiment, a relative dielectric constant of 1.5 or more) to a high dielectric constant (in one embodiment, a relative dielectric constant of 10,000 or less). In one embodiment, the polydispersity index is, in terms of reducing voids in the dielectric and thereby precisely controlling the dielectric constant, preferably 10% or more, or 11% or more, or 13% or more, or 15% or more. In terms of avoiding a non-uniform dielectric due to localization of the particles, in one embodiment, the polydispersity index of the particles is, in one embodiment, preferably 40% or less, or 35% or less, or 30% or less, or 25% or less. In the present disclosure, the polydispersity index is a value determined from the particle size measured by the cumulant method.

[0024] Examples of a method for controlling the polydispersity index of particles within the above range include a method in which a desired average particle diameter value is set, and particles (A) having a particle diameter smaller than that value are mixed with particles (B) having a particle diameter larger than that value, and the particle diameters of particles (A) and particles (B) and the mixing ratio of particles (A) / particles (B) are adjusted.

[0025] The mass ratio of the metal oxide particles in the dielectric is preferably 20% by mass or more and 95% by mass or less. From the viewpoint of easily adjusting the dielectric constant of the dielectric to a desired range by changing the average particle size of the metal oxide particles, and from the viewpoint of decomposing the organic components by energy irradiation and interacting with electromagnetic waves as a metal pattern, the mass ratio of the metal oxide particles is preferably 20% by mass or more, or 25% by mass or more, or 30% by mass or more, or 35% by mass or more, or 40% by mass or more, or 45% by mass or more, or 50% by mass or more. The mechanical strength of the dielectric is mainly expressed by the nonvolatile organic matter in the dielectric functioning as a binder. From the viewpoint of easily obtaining good mechanical strength by having a desired amount of nonvolatile organic matter present in the dielectric, the mass ratio of the metal oxide particles is preferably 95% by mass or less, or 90% by mass or less, or 85% by mass or less, or 80% by mass or less, or 75% by mass or less.

[0026] [Non-volatile organic matter] In the present disclosure, a non-volatile organic substance means a compound that does not have a boiling point or has a boiling point of 300° C. or higher. In the present disclosure, the boiling point is a value measured by a differential scanning calorimeter (DSC) or a differential thermal analysis (DTA). In one embodiment, a non-volatile organic substance is an organic substance that remains on a substrate when the non-volatile organic substance is applied to a substrate with a coating thickness of 0.1 mm and dried in air at normal pressure at 100° C. for 30 minutes. The non-volatile organic substance may be a single compound or a mixture of multiple compounds. In one embodiment, the non-volatile organic substance is a polymer.

[0027] The non-volatile organic material preferably has a structure capable of stabilizing the metal oxide particles by interacting with them. Examples of such structures include basic groups (e.g., amino groups, ammonium groups, amidoamino groups, etc.), hydrogen bond forming groups (e.g., hydroxyl groups, thiol groups, oxyethylene groups, amide groups, ester groups, aldehyde groups, etc.), coordinate bond forming groups (e.g., cyano groups, azo groups, nitro groups, etc.), acidic groups (e.g., carboxy groups, phenolic hydroxyl groups, sulfo groups), etc. More specific examples of non-volatile organic materials include: Polymers having basic groups, such as salts of long-chain polyaminoamides and polar acid esters, unsaturated polycarboxylic acid polyaminoamides, polycarboxylates of polyaminoamides, and salts of long-chain polyaminoamides and acid polymers; Polymers having a polyoxyethylene chain, such as polyethylene glycol and alkoxypolyethylene glycol; Alkylammonium salts, amine salts, or amidoamine salts of polymers such as acrylic polymers (homopolymers or copolymers), modified polyester acids, polyether ester acids, polyether carboxylic acids, and polycarboxylic acids; Compounds having a cyano group, such as cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, and cyanoethyl saccharose; From the viewpoint of easily changing the dielectric constant of the dielectric as desired, the non-volatile organic substance is preferably a polycarboxylate of a polyaminoamide, an alkylammonium salt, an amine salt or an amidoamine salt of a polymer such as a polycarboxylate, a compound having a cyano group, a polymer having a polyoxyethylene chain, or the like, more preferably a compound having a cyano group.

[0028] The non-volatile organic material may be a commercially available product. Commercially available products include, for example, DISPERBYK (registered trademark, the same applies below)-101, DISPERBYK-102, DISPERBYK-110, DISPERBYK-111, DISPERBYK-112, DISPERBYK-118, DISPERBYK-130, DISPERBYK-140, DISPERBYK-142, DISPERBYK-145, DISPERBYK-160, DISPERBYK-161, DISPERBYK-162, DISPERBYK-163, DISPERBYK-2155, DISPERBYK-2163, DISPERBYK-2164, DISPERBYK-180, DISPERBYK-2000, DISPERBYK-2025, DISPERBYK-2163, DISPERBYK-21 64, BYK-9076, BYK-9077, TERRA-204, TERRA-U (all manufactured by BYK-Chemie), FLOWRENE DOPA-15B, FLOWRENE DOPA-15BHFS, FLOWRENE DOPA-22, FLOWRENE DOPA-33, FLOWRENE DOPA-44, FLOWRENE DOPA-17HF, FLOWRENE TG-662C, FLOWRENE KTG-2400 (all manufactured by BYK-Chemie), Examples of suitable amines include ED-117, ED-118, ED-212, ED-213, ED-214, ED-216, ED-350, ED-360 (all manufactured by Kusumoto Chemicals), Plysurf M208F, Plysurf DBS (all manufactured by Daiichi Kogyo Seiyaku), CR-S, CR-M, CR-V, CR-U (all manufactured by Shin-Etsu Chemical Co., Ltd.), and U Imide Varnish (manufactured by Unitika Ltd.). These may be used alone or in combination.

[0029] The relative dielectric constant of the nonvolatile organic material is preferably 2 or more, or 2.5 or more, or 3 or more from the viewpoint of being able to increase the dielectric constant of the dielectric, and is preferably 30 or less, or 25 or less, or 20 or less from the viewpoint of reducing energy loss of electromagnetic waves in, for example, electromagnetic wave control applications.

[0030] The dielectric constant of a non-volatile organic material tends to be high when it has a highly polar functional group (e.g., amino group, hydroxy group, thiol group, cyano group, nitro group, carboxy group, phenolic hydroxyl group, sulfo group, etc.) in the molecule, and tends to be low when it does not have a highly polar functional group in the molecule. The non-volatile organic material may be selected according to the desired dielectric constant of the dielectric. Note that the above dielectric constant refers to the value of each non-volatile organic material when two or more types of non-volatile organic materials are used.

[0031] Non-volatile organic substances suitable for dielectrics with a relatively high dielectric constant (e.g., a dielectric constant of 6 or more) include compounds with a dielectric constant of 10 to 30, such as cyanoethyl pullulan (dielectric constant 18), cyanoethyl polyvinyl alcohol (dielectric constant 15), and cyanoethyl sucrose (dielectric constant 24). Non-volatile organic substances suitable for dielectrics with a relatively low dielectric constant (e.g., a dielectric constant of less than 4) include compounds with a dielectric constant of 4 or less, such as polytetrafluoroethylene (dielectric constant 2.1), tetrafluoroethylene-perfluoroalkylvinylether copolymer (dielectric constant 2.1), and tetrafluoroethylene-hexafluoropropylene copolymer (dielectric constant 2.1).

[0032] The mass ratio of the nonvolatile organic substance in the dielectric is preferably 5% by mass or more and 80% by mass or less. From the viewpoint that the nonvolatile organic substance acts as a binder and contributes to the mechanical strength of the dielectric, the mass ratio of the nonvolatile organic substance is preferably 5% by mass or more, or 10% by mass or more, or 15% by mass or more, or 20% by mass or more, or 25% by mass or more, and from the viewpoint of containing a desired amount of metal oxide particles and from the viewpoint of interlayer adhesion when a metal layer and a dielectric layer are laminated, the mass ratio of the nonvolatile organic substance is preferably 80% by mass or less, or 75% by mass or less, or 70% by mass or less, or 65% by mass or less, or 60% by mass or less, or 55% by mass or less, or 50% by mass or less.

[0033] [Dielectric morphology] The dielectric typically consists of metal oxide particles and a non-volatile organic substance, but the inclusion of additional components is not excluded as long as the effects of the present invention are not impaired. The dielectric may also be combined with a dispersion medium, such as water and / or a volatile organic substance (i.e., an organic substance not included in the non-volatile organic substance of the present disclosure). For example, a dielectric dispersion liquid obtained by adding 1 part by mass to 75 parts by mass of a dispersion medium to 100 parts by mass of a dielectric may be used for various purposes.

[0034] [Dielectric constant of dielectric material] The dielectric constant of the dielectric may be 1.5 or more in one embodiment, and may be 10,000 or less in one embodiment. The dielectric of the present embodiment may have a dielectric constant selected from a wide range depending on the application. For example, in insulating materials such as coating materials for electric wiring, coating materials for semiconductors, and substrates for laminates in electronic devices, a low dielectric constant is required to reduce dielectric loss, so the dielectric constant of the dielectric may be 1.5 to 5 in one embodiment. On the other hand, in capacitors, for example, a high dielectric constant is required to increase capacitance, so the dielectric constant of the dielectric may be 3 to 10,000 in one embodiment.

[0035] More specifically, in one embodiment, the relative dielectric constant of a dielectric applied to an insulating material (e.g., a coating material for electric wiring, a coating material for semiconductors, a substrate for a laminate in an electronic device, etc.) is preferably 1.5 or more, or 2 or more, or 2.5 or more, from the viewpoint of ease of manufacturing the dielectric, and is preferably 5 or less, or 4.5 or less, or 4 or less, from the viewpoint of reducing dielectric loss.

[0036] In one aspect, the relative dielectric constant of the dielectric applied to the interelectrode material of the capacitor is, from the viewpoint of increasing the capacitance, preferably 3 or more, or 10 or more, or 20 or more, or 30 or more, or 50 or more, or 100 or more, and from the viewpoint of ease of production of the dielectric, preferably 10,000 or less, or 1,000 or less, or 500 or less.

[0037] In one embodiment, the relative permittivity of the dielectric applied to the electromagnetic wave control material for the electromagnetic wave control element is preferably 2 or more, or 2.5 or more, or 3 or more, from the viewpoint of generating a desired phase shift of the reflected wave in the electromagnetic wave reflection application, and is preferably 100 or less, or 50 or less, or 30 or less, or 20 or less, or 10 or less, or 5 or less, from the viewpoint of reducing the energy loss of the electromagnetic wave. In the case of electromagnetic wave reflection application, when the dielectric constant is large, the phase shift of the reflected wave can be easily changed by only slightly changing the size of the dielectric, so that a wide range of phase shift is easily realized. Note that a known method may be used to evaluate the phase shift. Specifically, the software described in AF Oskooi et. al., “MEEP: A flexible free software package for electromagnetic simulations by the FDTD method”, Computer Physics Communications 181, 687-702 (2010), or HFSS manufactured by ANSYS, Inc. may be used as a method for obtaining an evaluation result equivalent thereto. In one embodiment, the phase of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz is incident at 0° may be calculated.

[0038] In a preferred embodiment, the metal oxide particles have a relative dielectric constant of 5-20, the nonvolatile organic material has a relative dielectric constant of 2-20, and the dielectric material has a relative dielectric constant of 3-20.

[0039] The dielectric of this embodiment can be easily manufactured as a dielectric with few voids because the polydispersity index of the particle diameter of the metal oxide particles is controlled within a predetermined range. Therefore, according to the dielectric of this embodiment, a uniform dielectric layer of a desired shape can be formed not only on a flat surface but also on a curved surface such as the surface of a three-dimensional object, and it is also possible to form a fine dielectric pattern. Therefore, the dielectric of this embodiment can be suitably applied to a wide range of applications such as dielectric members and electrical parts exemplified below.

[0040] <Dielectric materials and electrical components> One aspect of the present invention provides a dielectric member and an electric part containing the dielectric of this embodiment. In one aspect, the dielectric member containing the dielectric is an insulating material for electronic devices, an insulating material for semiconductor elements, an interelectrode material for capacitors, or an electromagnetic wave control material for electromagnetic wave control elements. More specifically, the dielectric may be used as: an insulating material such as a covering material for electric wiring, a covering material for semiconductors in semiconductor elements (i.e., a component of an electronic circuit formed of semiconductors); a substrate for a laminated plate in an electronic device; an interelectrode material for a capacitor (i.e., an electronic component that stores and discharges); an electromagnetic wave control material that refracts, abnormally reflects, or absorbs electromagnetic waves in an electromagnetic wave control element (i.e., an element that imparts directionality to incident electromagnetic waves, absorbs electromagnetic waves, converts electromagnetic waves into electrical energy, etc., such as an electromagnetic wave lens, an electromagnetic wave reflector, an electromagnetic wave absorbing plate, an antenna, etc.). In one aspect, the dielectric of this embodiment can be excellent in the performance of suppressing the energy loss of electromagnetic waves. Such a dielectric is particularly suitable for use in electromagnetic wave control elements such as electromagnetic wave reflecting elements. In one embodiment, the electrical component may be an electrical wiring, a semiconductor element, a capacitor, an electromagnetic wave control element, or the like. An exemplary embodiment of an electromagnetic wave control element, which is an example of the electrical component of this embodiment, will be described below.

[0041] [Electromagnetic wave control element] One aspect of the present invention provides an electromagnetic wave control element including a dielectric layer made of the dielectric of the present embodiment and a metal layer. In one aspect, the electromagnetic wave control element may further include a metal pattern disposed on the dielectric layer.

[0042] (metal layer) Examples of metals contained in the metal layer include silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium and germanium. Silver, copper, gold, platinum, aluminum, nickel and iron are preferred, silver, copper, gold, platinum and aluminum are more preferred, and silver, copper and gold are even more preferred, because they have high electrical conductivity and therefore easily resonate with electromagnetic waves.

[0043] The shape of the metal layer is not particularly limited, and may be a flat plate, a sheet, a layer extending on the surface of a three-dimensional object, or the like. The metal layer may be a commercially available metal plate or metal foil. The surface of the metal layer may be any shape, such as a flat surface, a curved surface, a surface including a step, or the like, and the dielectric layer can be disposed on any surface. Since the dielectric of this embodiment can form a dielectric layer having a uniform structure with few voids, a high-performance electromagnetic wave control element can be formed regardless of the shape of the dielectric layer formation surface of the metal layer. For example, when the electromagnetic wave control element is an electromagnetic wave reflection element, the metal layer may be disposed on the surface opposite to the electromagnetic wave incidence surface.

[0044] In the electromagnetic wave control element, the area of ​​the metal layer, more specifically, the total area of ​​the surface of the metal layer in contact with the dielectric layer, is preferably 100 mm2 or less, from the viewpoint of allowing the electromagnetic wave emitted from the electromagnetic wave control element (for example, the reflected wave in the electromagnetic wave reflecting element) to cover a wide area. 2 or more, or 500mm 2 or more, or 1000mm 2 or more, or 2500mm 2 or more, or 5000mm 2 or more, or 10,000 mm 2 From the viewpoint of ease of processing, it is preferably 100 m2 Less than or equal to 10m 2 Less than or equal to 1m 2 Less than or equal to 0.5m 2 Less than or equal to 0.25m 2 The dielectric of the present embodiment can have a uniform structure even when it is made into a dielectric layer having a large area, and therefore can exhibit good electromagnetic wave control performance even in an electromagnetic wave control element having a total area in the above range.

[0045] The thickness of the metal layer does not need to be constant within the layer. The thickness of the thinnest part of the metal layer is preferably 1 μm or more, or 5 μm or more, or 10 μm or more from the viewpoint of suppressing electromagnetic wave loss, and is preferably 1000 μm or less, or 500 μm or less, or 200 μm or less, or 100 μm or less, or 50 μm or less from the viewpoint of ease of processing.

[0046] (Dielectric layer) The dielectric layer is disposed on the metal layer, more specifically, disposed so that at least a portion of the dielectric layer is in contact with the surface of the metal layer. That is, for example, an air or vacuum layer may exist in the space between the metal layer and the dielectric layer. In one embodiment, the dielectric layer has a form of a dielectric pattern that is periodically disposed on the metal layer (that is, regularly arranged to form a repeating structure). With such a dielectric pattern, the degree of phase shift of the electromagnetic wave can be easily controlled by appropriately designing the shape and size of the pattern, so that an electromagnetic wave control element capable of emitting electromagnetic waves covering a wide area can be manufactured by a simple process.

[0047] The shape of the dielectric pattern may be appropriately selected as desired from a rectangle and other polygons, a circle, an ellipse, a ring, a split ring, a multiple split ring, and the like. The dielectric pattern may be formed by regularly arranging recesses of these shapes in the dielectric layer. The size of the dielectric pattern may be appropriately designed according to the degree of the desired phase shift. For example, in the case of a rectangle, the minor axis of the dielectric pattern is preferably 0.02 times or more, or 0.03 times or more, or 0.05 times or more, in one aspect, from the viewpoint of easily realizing the desired phase shift with respect to the wavelength of the incident electromagnetic wave, and from the above viewpoint, it may be preferably 1 time or less, or 0.7 times or less, or 0.5 times or less. Since the dielectric of this embodiment can form a uniform dielectric layer with few voids even when it is made into a fine-sized dielectric pattern, it can function as a metasurface by two-dimensionally arranging a dielectric pattern finer than the wavelength of the electromagnetic wave in a desired shape. Therefore, the shape of the dielectric pattern may be any shape that is understood by a person skilled in the art to function as a so-called metasurface.

[0048] The dielectric pattern may be periodically arranged for the purpose of generating a gradient in the phase shift of the electromagnetic wave emitted from the electromagnetic wave control element (for example, the reflected wave in the case of the electromagnetic wave reflecting element). In this case, the pattern period is preferably 1.06 times or more, or 1.15 times or more, or 1.74 times or more, and preferably 20 times or less, or 12 times or less, or 6 times or less, relative to the wavelength corresponding to the frequency of the electromagnetic wave incident on the electromagnetic wave reflecting element.

[0049] The area of ​​each of the four sides surrounding the periphery of the dielectric pattern is preferably 95 mm from the viewpoint of allowing the electromagnetic wave emitted from the electromagnetic wave control element (for example, the reflected wave in the electromagnetic wave reflecting element) to cover a wide area. 2 or more, or 475mm 2 or more, or 950mm 2 or more, or 2375mm 2 or more, or 4750mm 2 or more, or 9500mm 2 From the viewpoint of ease of processing, it is preferable that the thickness is 95 mm or more. 2Less than or equal to 9.5m 2 Less than or equal to 0.95m 2 Less than or equal to 0.4750m 2 Less than or equal to 0.2375m 2 The four sides surrounding the periphery of the dielectric pattern refer to a rectangle with the smallest area that includes all the dielectric patterns in a unit period. The area can be obtained by length measurement using an optical microscope. For example, the area may be obtained by measuring the length and width of the region surrounding the periphery and multiplying the length by the width.

[0050] From the viewpoint of easily achieving the desired phase shift, the thickness of the dielectric layer is preferably 75 nm or more, or 1 μm or more, or 3 μm or more, or 10 μm or more, and from the same viewpoint, it is preferably 43 mm or less, or 20 mm or less, or 8 mm or less.

[0051] (Metal Pattern) The metal pattern may be disposed at a position in contact with the dielectric layer, and the presence of the dielectric layer between the metal pattern and the metal layer results in a structure in which the metal pattern and the metal layer are not in contact with each other. The metal pattern does not necessarily have to be disposed on the surface of the dielectric layer, and may be disposed inside the dielectric layer (embedded in one embodiment).

[0052] The shape of the metal pattern is not particularly limited, and may be, for example, a polyhedron. The surface of the metal pattern may be a flat or curved surface. The metal pattern may have a cavity inside. In one embodiment, the metal pattern may function as a meta-atom. In this case, the size of the metal pattern may be appropriately designed according to the wavelength of the electromagnetic wave incident on the electromagnetic wave control element. The incident electromagnetic wave may be a millimeter wave to a terahertz wave, and the wavelength may be, for example, in the range of 11 mm to 100 μm. The value of the square root of the area of ​​the surface of each metal pattern in contact with the dielectric layer is preferably 0.02 times or more, or 0.03 times or more, or 0.05 times or more, relative to the wavelength of the incident electromagnetic wave, from the viewpoint of efficiently exciting surface plasmons by the incident electromagnetic wave, and from the above viewpoint, is preferably 1 time or less, or 0.7 times or less, or 0.5 times or less.

[0053] The metal pattern may be arranged periodically for the purpose of generating a gradient in the phase shift of the electromagnetic wave (for example, the reflected wave in the case of the electromagnetic wave reflecting element) emitted from the electromagnetic wave control element. In this case, the pattern period is preferably 1.06 times or more, or 1.15 times or more, or 1.74 times or more, and preferably 20 times or less, or 12 times or less, or 6 times or less, relative to the wavelength corresponding to the frequency of the electromagnetic wave incident on the electromagnetic wave reflecting element. According to the electromagnetic wave reflecting element of this embodiment, the reflection direction of the reflected wave of a desired frequency can be easily designed by adjusting the size and period of the metal pattern, so that an electromagnetic wave reflecting element capable of abnormally reflecting the electromagnetic wave in a desired direction (i.e., reflecting in a direction different from the specular reflection) can be manufactured by a simple process.

[0054] The area of ​​each of the four sides surrounding the periphery of the metal pattern is preferably 95 mm from the viewpoint of allowing the electromagnetic wave emitted from the electromagnetic wave control element (for example, the reflected wave from the electromagnetic wave reflecting element) to cover a wide area. 2 or more, or 475mm 2 or more, or 950mm 2 or more, or 2375mm 2 or more, or 4750mm 2 or more, or 9500mm 2 From the viewpoint of ease of processing, it is preferable that the thickness is 95 mm or more. 2 Less than or equal to 9.5m 2 Less than or equal to 0.95m 2 Less than or equal to 0.4750m 2 Less than or equal to 0.2375m 2 The four sides surrounding the periphery of the metal pattern refer to a rectangle with the smallest area that includes all the metal patterns within a unit period. The above area can be measured in the same manner as the area of ​​the dielectric pattern.

[0055] From the viewpoint of ease of forming the metal pattern, the volume resistivity of the metal pattern is preferably 2×10 -8 From the viewpoint of suppressing the energy of the electromagnetic wave incident on the electromagnetic wave control element from being converted into thermal energy and attenuated, it is preferably 1×10 -3 Ω m or less, or 1×10-4 Ω m or less, or 1×10 -5 Ω m or less, or 1×10 -6 Ω m or less.

[0056] The metal elements constituting the metal pattern are not particularly limited, and examples thereof include silver, copper, gold, aluminum, magnesium, zinc, cobalt, nickel, lithium, platinum, palladium, tin, chromium, lead, hafnium, zirconium, bismuth, manganese, titanium, molybdenum, antimony, indium, gallium, calcium, rhodium, iridium, sodium, tungsten, ruthenium, potassium, cadmium, osmium, rubidium, tantalum, strontium, thorium, niobium, protactinium, rhenium, vanadium, barium, arsenic, antimony, lutetium, yttrium, lanthanum, neodymium, thulium, holmium, dysprosium, and germanium. From the viewpoint of being less likely to attenuate surface plasmons excited by electromagnetic waves, silver, copper, gold, platinum, aluminum, nickel, and iron are preferred, silver, copper, gold, platinum, and aluminum are more preferred, and silver, copper, and gold are even more preferred.

[0057] In addition, it is preferable that the metal pattern contains the same metal element as the dielectric layer. This ensures good stability of the metal pattern even when the metal in the dielectric layer precipitates due to deterioration of the dielectric layer over time. In particular, it is more preferable that both the metal pattern and the dielectric layer contain copper elements. Copper has a low volume resistivity, so it is difficult to attenuate surface plasmons on the metal pattern excited by electromagnetic waves.

[0058] (Additional layers or components) The electromagnetic wave control element may further include an additional layer or member in addition to the metal layer, the dielectric layer, and the metal pattern. For example, an adhesive layer may be disposed between the metal layer and the dielectric layer. Examples of the adhesive layer include layers of acrylic resin, chloroprene rubber, silicone rubber, and the like. The presence of the adhesive layer stably holds the metal layer and the dielectric layer together, so that the electromagnetic wave control performance of the electromagnetic wave control element can be better expressed. In addition, the metal pattern may be covered with a resin layer or resin member for the purpose of preventing oxidation, etc. Examples of the resin in this case include epoxy resin, polyethylene terephthalate (PET) resin, and the like.

[0059] (operating frequency) The operating frequency of the electromagnetic wave control element may be from the visible light band to the terahertz wave band. From the viewpoint of suitability for high-speed communication applications, the operating frequency is preferably 0.7 GHz or more, or 1.5 GHz or more, or 3.6 GHz or more, or 27 GHz or more, or 92 GHz or more, or 152 GHz or more, or 287 GHz or more. From the viewpoint of suppressing attenuation of electromagnetic waves, the operating frequency is preferably 400 THz or less, or 10 THz or less, or 3 THz or less.

[0060] (electromagnetic wave reflection angle) When the electromagnetic wave control element is an electromagnetic wave reflecting element, for electromagnetic waves of any frequency between 0.7 GHz and 400 THz, the reflection angle of the electromagnetic wave incident on the element at 0° is preferably 3° or more, 5° or more, or 10° or more from the viewpoint of increasing the gain as an electromagnetic wave reflector, and is preferably 70° or less, 60° or less, or 35° or less from the above viewpoint. The electromagnetic wave reflecting element of this embodiment is excellent in the ability to wrap around shielding objects even for electromagnetic waves in a high frequency band with high linearity.

[0061] <Electromagnetic wave transmission and reception system> One aspect of the present invention provides an electromagnetic wave transmission / reception system including the electromagnetic wave control element of the present embodiment and an electromagnetic wave transmission antenna. The type and shape of the antenna are not particularly limited and may be appropriately selected depending on the purpose. For example, the antenna may be a microstrip antenna.

[0062] <Method of manufacturing electromagnetic wave control element> One aspect of the present invention provides a method for manufacturing an electromagnetic wave control element including a dielectric layer made of the dielectric of this embodiment and a metal layer, the method including a step of forming the dielectric layer on the metal layer.

[0063] [Process for forming dielectric layer] In this step, a dielectric layer is formed on the metal layer. Examples of methods for forming the dielectric layer include a method of printing a dielectric on a metal layer (printing method), a method of depositing a dielectric on a metal layer (deposition method), and a method of pressing a metal layer and a dielectric layer with a rolling machine to adhere them to each other (pressing method). In the pressing method, an adhesive layer may be sandwiched between the metal layer and the dielectric layer and pressed with the rolling machine. In this case, the metal layer and the dielectric layer can be held more firmly. The printing method is particularly preferable in that the dielectric can be uniformly applied by an inexpensive process even if the surface of the metal layer is large. According to the printing method, the dielectric layer can be formed directly on the metal layer with high accuracy, so that the productivity can be improved compared to, for example, a method of performing development and etching using a mask. In addition, for example, a vacuum process is required in the deposition method, but such a vacuum process is not required in the printing method, which is advantageous in terms of manufacturing costs.

[0064] In the printing method, the dielectric may be applied to a part or the whole area of ​​the metal layer to form a coating film. The dielectric used in the printing method may have a viscosity adjusted to have a desired fluidity, and may be used as it is or dispersed in a dispersion medium.

[0065] More specifically, the dielectric coating method may include an aerosol method, screen printing, intaglio direct printing, intaglio offset printing, flexographic printing, flatbed offset printing, and dispenser drawing. Coating mechanisms may include die coating, spin coating, slit coating, bar coating, knife coating, spray coating, and dip coating. The coating may be dried by a drying process, if necessary.

[0066] [Metal pattern forming process] When the electromagnetic wave control element further includes a metal pattern, the manufacturing method of the electromagnetic wave control element further includes a step of forming the metal pattern. In one embodiment, the metal pattern is formed on and / or within the dielectric layer by irradiating the dielectric layer with energy. Examples of the method of forming the metal pattern by energy irradiation include a thermal sintering method, a plasma sintering method, and a light sintering method.

[0067] In the thermal firing method, a part of the metal oxide in the dielectric layer is reduced to metal using a firing furnace. In this method, a heat-reflecting masking film on which a figure corresponding to the desired metal pattern shape is drawn is placed on the dielectric layer, and infrared radiation is applied from above the heat-reflecting masking film to perform patterning. This allows the formation of a laminated structure in which a metal layer, a dielectric layer, and a metal pattern are arranged in this order. In order to sinter the metal, the coating film is thermally fired at heat of, for example, 100°C or higher, preferably 150°C or higher, and more preferably 200°C or higher. In one embodiment, the temperature of the thermal firing may be 1000°C or lower, 600°C or lower, or 400°C or lower, from the viewpoint of process efficiency. The thermal firing temperature can be confirmed by measuring the temperature of the dielectric layer during firing with a thermocouple. Since thermal firing is easily affected by oxygen, it is preferable to thermally fire the dielectric layer in a non-oxidizing atmosphere. The reduction of the metal oxide proceeds with the contribution of the organic matter present in the dielectric layer, but when the reduction does not proceed easily with only the organic matter, it is preferable to perform the thermal firing in a reducing atmosphere. The non-oxidizing atmosphere is an atmosphere that does not contain an oxidizing gas such as oxygen, for example, an atmosphere filled with an inert gas such as nitrogen, argon, helium, or neon. The reducing atmosphere refers to an atmosphere in which a reducing gas such as hydrogen or carbon monoxide is present, and is an atmosphere filled with only a reducing gas or a mixture of a reducing gas and an inert gas. These gases may be filled in a firing furnace, and the dielectric layer may be thermally fired in a closed system or while the gas is continuously flowing. The thermal firing may be performed in any atmosphere of normal pressure, pressurized pressure, or reduced pressure.

[0068] In the plasma sintering method, a plasma absorbing material (e.g., glass, resin, etc.) on which a figure corresponding to the desired metal pattern shape is drawn is placed on a dielectric layer, and patterning is performed by irradiating the plasma from above the plasma absorbing material. This allows the formation of a laminated structure in which a metal layer, a dielectric layer, and a metal pattern are arranged in this order. Compared with the thermal sintering method, the plasma sintering method allows processing at a lower temperature, and may be more advantageous than the thermal sintering method when a dielectric with low heat resistance is used. In addition, according to the plasma sintering method, since it is possible to remove organic matter, oxide film, etc. on the pattern surface by plasma, there is also the advantage that good solderability can be ensured, for example, when an electromagnetic wave control element is further soldered. Specifically, a reducing gas or a mixed gas of a reducing gas and an inert gas is flowed into a chamber, plasma is generated by microwaves, and the active species generated by this are used as a heat source required for reduction or sintering to form a metal pattern. Hydrogen, etc. can be used as the reducing gas, and nitrogen, helium, argon, etc. can be used as the inert gas. These may be used alone or by mixing the reducing gas and the inert gas in any ratio. Two or more inert gas components may be mixed and used.

[0069] In the plasma sintering method, active species are deactivated especially in the metal parts, and the metal parts are selectively heated. As the sintering process progresses, the metal oxide in the dielectric layer changes to metal, facilitating the heating of only the metal pattern parts. In addition, if organic matter remains in the metal pattern, it will hinder sintering and the electrical resistance of the metal pattern will tend to increase, but the plasma sintering method is very effective at removing organic matter from the metal pattern.

[0070] In the plasma sintering method, the microwave input power, the flow rate of the introduced gas, the pressure inside the chamber, the distance from the plasma source to the sample to be treated, the temperature of the sample to be treated, and the treatment time can be adjusted, and the intensity of the treatment can be changed by adjusting these. Therefore, by optimizing the above adjustment items, it is possible to obtain metal patterns of various thicknesses. However, the optimal conditions differ depending on the type and / or amount of metal oxide particles and non-volatile organic substances in the dielectric layer, so it is best to adjust them according to the purpose.

[0071] In the light sintering method, light irradiation is performed as the energy irradiation. A flash light method using a discharge tube such as xenon as a light source, or a laser light method can be applied. These methods involve short-term exposure to high-intensity light, raising the temperature of the dielectric layer to a high temperature in a short time, and sintering, which reduces and sinters the metal oxide in the dielectric layer, integrates them, and decomposes the organic matter to form a metal pattern. When the light sintering method is performed by laser irradiation, sintering and patterning can be performed at the same time by irradiating the laser on the dielectric layer. By adjusting the energy irradiation intensity, it is possible to leave an unreduced dielectric layer under the metal pattern. This allows the formation of a laminated structure in which a metal layer, a dielectric layer, and a metal pattern are arranged in this order.

[0072] The flash light method uses a xenon discharge tube to instantly discharge the charge stored in a capacitor, generating a large amount of pulsed light, which is then irradiated onto the dielectric layer to instantly heat the metal oxide in the dielectric layer to a high temperature, changing it into a metal pattern. The amount of exposure can be adjusted by the light intensity, light emission time, light irradiation interval, and number of times.

[0073] Although the light source is different, the same effect as the flash light method can be obtained by using a laser light source. In the case of a laser, in addition to the adjustment items of the flash light method, there is a degree of freedom in wavelength selection, and the emission wavelength can be selected taking into account the light absorption wavelength of the dielectric layer. In addition, exposure by beam scanning is possible, and it is characterized by easy adjustment of the exposure range, such as selection of exposure to the entire dielectric layer or partial exposure. Types of lasers that can be used include YAG (yttrium aluminum garnet) lasers, YVO (yttrium vanadate) lasers, Yb (ytterbium) lasers, semiconductor (GaAs, GaAlAs, GaInAs) lasers, and carbon dioxide lasers, and not only the fundamental wave but also higher harmonics can be extracted and used as necessary.

[0074] In particular, when using a laser beam, the emission wavelength is preferably 300 nm or more and 1500 nm or less, for example, 355 nm, 405 nm, 445 nm, 450 nm, 532 nm, 1056 nm, etc. are preferable. From the absorption region of the dielectric layer, laser wavelengths of 355 nm, 405 nm, 445 nm, 450 nm, and / or 532 nm are particularly preferable. By using the laser beam, a desired pattern can be freely created in a plane or a three-dimensional form.

[0075] From the viewpoint of making it easier to apply solder and increasing solder adhesion when the electromagnetic wave control element is further soldered, the arithmetic mean surface roughness (Ra) of the metal pattern is preferably 1 nm or more and 500 nm or less. In the present disclosure, the arithmetic mean surface roughness is a value measured using a surface roughness measuring instrument by a method conforming to Japanese Industrial Standards (JIS) B0601. EXAMPLES

[0076] The exemplary embodiments of the present invention will be further described below with reference to examples, but the present invention is not limited to these examples.

[0077] [Evaluation method] (Average particle size and polydispersity index of metal oxide particles) The average particle size and polydispersity index of the metal oxide particles were measured by dispersing the metal oxide particles in a solvent and using a nanoSAQLA manufactured by Otsuka Electronics Co., Ltd. by the cumulant method.

[0078] (Dielectric constant) The relative dielectric constant was calculated from the time waveform of the transmitted electric field when terahertz waves (frequency 0.5 THz) were transmitted through the sample using a TAS7500SL manufactured by Advantest Corporation.

[0079] [Example 1] (Preparation of Dielectric) 202 g of copper acetate (II) monohydrate (Kanto Chemical Co., Ltd.) was dissolved in a mixed solvent of 1890 g of distilled water (Kyoei Pharmaceutical Co., Ltd.) and 874 g of 1,2-propylene glycol (Kanto Chemical Co., Ltd.), and the liquid temperature was adjusted to -5°C using an external temperature controller. 59 g of hydrazine monohydrate (Tokyo Chemical Industry Co., Ltd.) was added to the obtained solution over 20 minutes, and the mixture was stirred for 30 minutes under a nitrogen atmosphere, after which the liquid temperature was adjusted to 25°C using an external temperature controller and stirred for 90 minutes. After stirring, the obtained dispersion was separated into a supernatant and a precipitate by centrifugation. A mixture of 6 g of DISPERBYK-145 (BYK-Chemie) (as a non-volatile organic substance) and 219 g of ethanol (FUJIFILM Wako Pure Chemical Industries, Ltd.) was added to 98 g of the obtained precipitate, and the mixture was dispersed using a homogenizer. A mixture of 15 g of methoxypolyethylene glycol (manufactured by Aoki Oil Co., Ltd.) (as a non-volatile organic substance) and 15 g of terpineol (manufactured by Nippon Fragrance Pharmaceutical Co., Ltd.) (as a solvent) was added, and the volatile solvent was removed using a rotary evaporator. 101 g of a composition containing 64% by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 21.4 nm, the polydispersity index was 13.7%, and the relative dielectric constant was 7.6.

[0080] The obtained composition was applied to a polyimide substrate (manufactured by Toray DuPont Co., Ltd.) using an applicator and dried in an oven at 60°C for 4 hours to form a dielectric on the polyimide substrate. The obtained dielectric was removed together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 5.1. The relative dielectric constants of methoxypolyethylene glycol and DISPERBYK-145 itself were 2.9 and 4.6, respectively.

[0081] (Design of electromagnetic wave control elements) FIG. 1 is a diagram for explaining the laminate produced in Example 1, where (A) is a perspective view and (B) is a BB cut end view of (A). Also, FIG. 2 is a diagram for explaining the metal pattern in the laminate produced in Example 1. With reference to FIGS. 1 and 2, a laminate 1 was designed in which a dielectric layer 12 (thickness of metal pattern non-forming portion R1: 28 μm, thickness of metal pattern forming portion R2: 25 μm, relative dielectric constant: 5.1) was arranged on a metal layer 11 (thickness: 18 μm, copper), and a metal pattern 13 (a metal pattern in which rectangular parallelepiped copper structures having a thickness of 1.5 μm, a vertical length L, and a horizontal length of 90 μm are regularly arranged in a repeat unit P1 with a vertical period of 200 μm and a horizontal period of 120 μm) was arranged thereon. In the above design, the thickness of the dielectric layer 12 was made different between the metal pattern non-forming portion R1 and the metal pattern forming portion R2 as described above, simulating the manner in which a metal pattern is arranged in a form embedded in a dielectric layer.

[0082] Using HFSS made by ANSYS, we calculated the phase of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° on this laminate. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 3.

[0083] Based on the results shown in FIG. 3, five vertical lengths L of the metal pattern 13 were selected (73 μm, 96 μm, 102 μm, 112 μm, 148 μm), as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of a repeating unit P21 in which two of these are arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz is incident at 0° is calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 5. The vertical axis in FIG. 5 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 5, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0084] Next, a laminate was designed that exhibits abnormal reflection at 14.5° to the right in Fig. 4 at a frequency of 0.1 THz. With reference to Figs. 1 and 2, a laminate 1 was designed in which a dielectric layer 12 (metal pattern non-forming portion R1 has a thickness of 128 µm, a metal pattern forming portion R2 has a thickness of 125 µm, and a relative dielectric constant of 5.1) was arranged on a metal layer 11 (thickness 18 µm, copper), and a metal pattern 13 (a metal pattern in which rectangular parallelepiped copper structures having a thickness of 1.5 µm, a vertical length L, and a horizontal length of 450 µm are regularly arranged in a repeat unit P1 with a vertical period of 1000 µm and a horizontal period of 600 µm) was arranged thereon.

[0085] Using HFSS made by ANSYS, we calculated the phase of the reflected wave when an electromagnetic wave with a frequency of 0.1 THz was incident at 0° on this laminate. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 6.

[0086] Based on the results shown in FIG. 6, five vertical lengths L of the metal pattern 13 were selected (422 μm, 514 μm, 550 μm, 591 μm, 850 μm), as shown in FIG. 7, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of a repeating unit P21 in which four of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.1 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 7. The results are shown in FIG. 8. The vertical axis in FIG. 8 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 8, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected at 14.5° to the right in FIG. 7.

[0087] Next, a laminate was designed that exhibits abnormal reflection at 60° to the right in Fig. 4 at a frequency of 8.5 GHz. Referring to Figs. 1 and 2, a laminate 1 was designed in which a dielectric layer 12 (metal pattern non-forming portion R1 has a thickness of 1503 µm, a metal pattern forming portion R2 has a thickness of 1500 µm, and a relative dielectric constant of 5.1) was arranged on a metal layer 11 (thickness 18 µm, copper), and a metal pattern 13 (a metal pattern in which rectangular parallelepiped copper structures having a thickness of 1.5 µm, a vertical length L, and a horizontal length of 6300 µm are regularly arranged in a repeat unit P1 with a vertical period of 12000 µm and a horizontal period of 8150 µm) was arranged thereon.

[0088] Using HFSS manufactured by ANSYS, we calculated the phase of the reflected wave when an electromagnetic wave with a frequency of 8.5 GHz was incident at 0° on this laminate. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 9.

[0089] Based on the results shown in FIG. 9, as shown in FIG. 10, five vertical lengths L of the metal pattern 13 were selected (2100 μm, 5910 μm, 6400 μm, 6810 μm, 7860 μm), and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of repeating units P21 in which each of these was arranged one by one. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 8.5 GHz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 10. The results are shown in FIG. 11. Note that the vertical axis in FIG. 11 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 11, it was confirmed that an incident wave at 0° (i.e., an incident wave perpendicular to the laminate) was abnormally reflected at 60° to the right in FIG. 10.

[0090] (Preparation of Laminate) Based on the above design, a laminate was fabricated that exhibits abnormal reflection at 30° at a frequency of 0.5 THz. Referring again to FIGS. 1 and 4, a metal layer 11 (area 900 mm 2The composition prepared above was applied using an applicator onto a copper foil (18 μm thick, AS ONE Corporation), and dried in an oven at 60° C. for 4 hours to form a dielectric layer 12 (28 μm thick, dielectric constant 5.1). Next, the dielectric layer 12 was irradiated with a laser beam having a wavelength of 355 nm to form a metal pattern 13 (a metal pattern consisting of repeating units in which five rectangular metal structures with a thickness of 1.5 μm, a vertical length L, and a horizontal length of 90 μm were selected (73 μm, 96 μm, 102 μm, 112 μm, 148 μm) and two of them were arranged). Due to the formation of the metal pattern 13 by irradiating the dielectric layer 12 with a laser, the thickness of the portion of the dielectric layer 12 under the metal pattern (i.e., the portion corresponding to the metal pattern forming portion R2) became 25 μm.

[0091] [Example 2] (Preparation of Dielectric) A mixture of 18 g of DISPERBYK-145 (manufactured by BYK-Chemie) (as a non-volatile organic substance) and 207 g of heptanol (manufactured by Toyo Gosei Co., Ltd.) was added to 98 g of the precipitate obtained by the same operation as in Example 1, and the mixture was dispersed using a homogenizer. 323 g of a composition containing 20% ​​by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 32.6 nm, the polydispersity index was 10.8%, and the relative dielectric constant was 7.6.

[0092] Using the obtained composition, a dielectric was formed on a polyimide substrate in the same manner as in Example 1. The obtained dielectric was taken out together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 4.9.

[0093] (Design of electromagnetic wave control elements) Except for the relative dielectric constant of the dielectric, the laminate shown in Figures 1 and 2 was subjected to phase calculation of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° using HFSS manufactured by ANSYS, Inc. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 12.

[0094] Based on the results shown in FIG. 12, five vertical lengths L of the metal pattern 13 were selected (67 μm, 98 μm, 106 μm, 114 μm, 142 μm) as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of repeating units P21 in which two of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 13. The vertical axis in FIG. 13 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 13, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0095] [Example 3] (Preparation of Dielectric) A mixture of 18 g of DISPERBYK-145 (manufactured by BYK-Chemie) (as a non-volatile organic substance) and 210 g of heptanol (manufactured by Toyo Gosei) was added to 98 g of the precipitate obtained by the same procedure as in Example 1, and the mixture was dispersed using a homogenizer. 326 g of a composition containing 20% ​​by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 32.2 nm, the polydispersity index was 12.6%, and the relative dielectric constant was 7.6.

[0096] A dielectric was formed on a polyimide substrate by the same operation as in Example 1. The resulting dielectric was taken out together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 5.1.

[0097] (Design of electromagnetic wave control elements) Since the relative dielectric constant of the dielectric was the same as that of Example 1, the same design as that of Example 1 enabled an incident wave at 0° (i.e., an incident wave perpendicular to the laminate) to be abnormally reflected 30° to the right in FIG. 4, as shown in FIG. 5.

[0098] [Example 4] (Preparation of Dielectric) A mixture of 13 g of DISPERBYK-145 (manufactured by BYK-Chemie) (as a non-volatile organic substance) and 212 g of ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 98 g of the precipitate obtained by the same operation as in Example 1, and the mixture was dispersed using a homogenizer. 323 g of a composition containing 20% ​​by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 22.3 nm, the polydispersity index was 16.7%, and the relative dielectric constant was 7.6.

[0099] A dielectric was formed on a polyimide substrate by the same operation as in Example 1. The resulting dielectric was taken out together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 5.2.

[0100] (Design of electromagnetic wave control elements) Except for the relative dielectric constant of the dielectric, the laminate shown in Figures 1 and 2 was subjected to phase calculation of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° using HFSS manufactured by ANSYS, Inc. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 14.

[0101] Based on the results shown in FIG. 14, five vertical lengths L of the metal pattern 13 were selected (73 μm, 96 μm, 103 μm, 111 μm, 148 μm) as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of repeating units P21 in which two of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 15. The vertical axis in FIG. 15 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 15, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0102] [Example 5] (Preparation of Dielectric) A mixture of 13 g of DISPERBYK-145 (manufactured by BYK-Chemie) (as a non-volatile organic substance) and 212 g of diethylene glycol (manufactured by Merck) was added to 98 g of precipitate obtained by the same procedure as in Example 1, except that the liquid temperature before adding hydrazine monohydrate was 5°C, and the mixture was dispersed using a homogenizer. 323 g of a composition containing 20% ​​by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 38.2 nm, the polydispersity index was 26.4%, and the relative dielectric constant was 7.6.

[0103] A dielectric was formed on a polyimide substrate by the same operation as in Example 1. The resulting dielectric was taken out together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 5.5.

[0104] (Design of electromagnetic wave control elements) Except for the relative dielectric constant of the dielectric, the laminate shown in Figures 1 and 2 was subjected to phase calculation of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° using HFSS manufactured by ANSYS, Inc. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 16.

[0105] Based on the results shown in FIG. 16, five vertical lengths L of the metal pattern 13 were selected (76 μm, 93 μm, 100 μm, 108 μm, 168 μm) as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of repeating units P21 in which two of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 17. The vertical axis in FIG. 17 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 17, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0106] [Example 6] (Preparation of Dielectric) A mixture of 13 g of DISPERBYK-145 (manufactured by BYK-Chemie) (as a non-volatile organic substance) and 212 g of ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 98 g of precipitate obtained by the same procedure as in Example 1, except that the amount of copper (II) acetate monohydrate added to the mixed solvent was 290 g, and the amount of hydrazine monohydrate added thereafter was 85 g, and the mixture was dispersed using a homogenizer. 323 g of a composition containing 20% ​​by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 169 nm, the polydispersity index was 31.4%, and the relative dielectric constant was 7.6.

[0107] A dielectric was formed on a polyimide substrate by the same operation as in Example 1. The resulting dielectric was taken out together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 5.5.

[0108] (Design of electromagnetic wave control elements) Since the relative dielectric constant of the dielectric was the same as that of Example 5, the same design as that of Example 5 made it possible to abnormally reflect an incident wave at 0° (i.e., an incident wave perpendicular to the laminate) to the right in the direction 30° in FIG. 4, as shown in FIG. 17.

[0109] [Example 7] (Preparation of Dielectric) Except for changing the amount of hydrazine monohydrate added to 29 g, the same procedure as in Example 5 was repeated to obtain 323 g of a composition. The cuprous oxide particles had an average particle size of 51.7 nm, a polydispersity index of 39.7%, and a relative dielectric constant of 7.6.

[0110] A dielectric was formed on a polyimide substrate by the same operation as in Example 1. The resulting dielectric was taken out together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 6.0.

[0111] (Design of electromagnetic wave control elements) Except for the relative dielectric constant of the dielectric, the laminate shown in Figures 1 and 2 was subjected to phase calculation of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° using HFSS manufactured by ANSYS, Inc. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 18.

[0112] Based on the results shown in FIG. 18, five vertical lengths L of the metal pattern 13 were selected (63 μm, 87 μm, 94 μm, 101 μm, 128 μm) as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of repeating units P21 in which two of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 19. The vertical axis in FIG. 19 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 19, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0113] [Example 8] (Preparation of Dielectric) A mixture of 13 g of DISPERBYK-145 (manufactured by BYK-Chemie) (as a non-volatile organic substance), 212 g of diethylene glycol (manufactured by Merck) and 129 g of acetic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to 98 g of the precipitate obtained by the same operation as in Example 1, and the mixture was dispersed using a homogenizer. 452 g of a composition containing 14% by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 3050 nm, the polydispersity index was 25.4%, and the relative dielectric constant was 7.6.

[0114] A dielectric was formed on a polyimide substrate by the same operation as in Example 1. The resulting dielectric was taken out together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 3.0.

[0115] (Design of electromagnetic wave control elements) Except for the relative dielectric constant of the dielectric, the laminate shown in Figures 1 and 2 was subjected to phase calculation of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° using HFSS manufactured by ANSYS, Inc. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 20.

[0116] Based on the results shown in FIG. 20, five vertical lengths L of the metal pattern 13 were selected (83 μm, 127 μm, 138 μm, 148 μm, 177 μm) as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of a repeating unit P21 in which two of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 21. The vertical axis in FIG. 21 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 21, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0117] [Example 9] (Preparation of Dielectric) A mixture of 13 g of DISPERBYK-145 (manufactured by BYK-Chemie) (as a non-volatile organic substance), 7 g of CR-U (manufactured by Shin-Etsu Chemical Co., Ltd.) (as a non-volatile organic substance), and 212 g of ethylene glycol monomethyl ether (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to 98 g of the precipitate obtained by the same operation as in Example 1, and the mixture was dispersed using a homogenizer. 330 g of a composition containing 20% ​​by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 20.8 nm, the polydispersity index was 14.8%, and the relative dielectric constant was 7.6.

[0118] A dielectric was formed on a polyimide substrate by the same procedure as in Example 1. The dielectric was removed together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 6.8. The relative dielectric constant of CR-U itself was 24.

[0119] (Design of electromagnetic wave control elements) Except for the relative dielectric constant of the dielectric, the laminate shown in Figures 1 and 2 was subjected to phase calculation of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° using HFSS manufactured by ANSYS, Inc. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 22.

[0120] Based on the results shown in FIG. 22, five vertical lengths L of the metal pattern 13 were selected (63 μm, 81 μm, 87 μm, 94 μm, 124 μm) as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of repeating units P21 in which two of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 23. The vertical axis in FIG. 23 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 23, it was confirmed that an incident wave at 0° (i.e., an incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0121] [Example 10] (Preparation of Dielectric) 80g of U-imide varnish (Unitika) was added to 120g of titanium oxide particles (Sigma-Aldrich) and dispersed using a planetary mixer. 200g of a composition containing 60% titanium oxide particles was obtained. The average particle size of the titanium oxide particles was 228nm, the polydispersity index was 34.2%, and the relative dielectric constant was 48.

[0122] The mixture was applied to a polyimide substrate (manufactured by DuPont-Toray Co., Ltd.) using an applicator, and cured on a hot plate at 40°C for 10 minutes, then at 80°C for 10 minutes to form a dielectric on the polyimide substrate. The resulting dielectric was removed from the polyimide substrate, and the dielectric constant of the dielectric was measured, which was 14. The dielectric constant of the U imide varnish cured under the same curing conditions (hereinafter referred to as the cured product U) itself was 5.5.

[0123] (Design of electromagnetic wave control elements) Except for the relative dielectric constant of the dielectric, the laminate shown in Figures 1 and 2 was subjected to phase calculation of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° using HFSS manufactured by ANSYS, Inc. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 24.

[0124] Based on the results shown in FIG. 24, five vertical lengths L of the metal pattern 13 were selected (24 μm, 46 μm, 50 μm, 54 μm, 65 μm) as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of repeating units P21 in which two of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 25. The vertical axis in FIG. 25 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 25, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0125] [Example 11] (Preparation of Dielectric) 80g of U-imide varnish (Unitika) was added to 120g of zinc oxide particles (FUJIFILM Wako Pure Chemical Industries, Ltd.), and dispersed using a planetary mixer. 200g of a composition containing 60% zinc oxide particles was obtained. The average particle size of the zinc oxide particles was 228nm, the polydispersity index was 34.2%, and the relative dielectric constant was 2.0.

[0126] A dielectric was formed by the same procedure as in Example 10. The resulting dielectric was taken out together with the polyimide substrate, and the relative dielectric constant of the dielectric was measured, which was 2.4.

[0127] (Design of electromagnetic wave control elements) Except for the relative dielectric constant of the dielectric, the laminate shown in Figures 1 and 2 was subjected to phase calculation of the reflected wave when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° using HFSS manufactured by ANSYS, Inc. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in Figure 2. The results are shown in Figure 26.

[0128] Based on the results shown in FIG. 26, five vertical lengths L of the metal pattern 13 were selected (88 μm, 140 μm, 152 μm, 162 μm, 186 μm) as shown in FIG. 4, and an electromagnetic wave control element was designed having a metal pattern structure P22 consisting of repeating units P21 in which two of these were arranged. The angular distribution of the reflected wave intensity when an electromagnetic wave with a frequency of 0.5 THz was incident at 0° was calculated. The polarization direction of the electric field of the electromagnetic wave is parallel to the length L in FIG. 4. The results are shown in FIG. 27. The vertical axis in FIG. 27 is a value proportional to the electromagnetic wave intensity. As shown in FIG. 27, it was confirmed that the incident wave at 0° (i.e., the incident wave perpendicular to the laminate) was abnormally reflected to the right at 30° in FIG. 4.

[0129] As can be seen from Examples 1 to 5 and 7, as the polydispersity index increases, the metal oxide particles tend to be densely packed due to the stone wall effect, the voids decrease, and the dielectric constant increases. As the dielectric constant increases as in Examples 1 to 7, 9, and 10, the portion with a large phase change shifts to the left as seen in Figures 3, 6, 9, 12, 14, 16, 18, 22, and 24. This reduces the length L in Figure 4, making it easier for the effects of dimensional deviations during laminate fabrication to become more pronounced. On the other hand, when the dielectric constant decreases as in Example 11, the portion with a large phase change shifts to the right as seen in Figure 26. This makes the longest L in Figure 4 close to 200 μm, making the vertical pattern spacing too small and making it easier for the pattern to be crushed depending on dimensional errors during fabrication.

[0130] [Comparative Example 1] 225 g of diethylene glycol (Tokyo Chemical Industry Co., Ltd.) was added to 98 g of the precipitate obtained by the same method as in Example 1, and the mixture was dispersed using a homogenizer to obtain 323 g of a composition containing 20% ​​by mass of cuprous oxide particles. The cuprous oxide particles had an average particle size of 19.0 nm and a polydispersity index of 18.0%.

[0131] The obtained composition was applied onto a polyimide substrate (manufactured by DuPont-Toray Co., Ltd.) using an applicator and dried overnight in an oven at 60°C. However, the dielectric cracked and the dielectric constant could not be measured.

[0132] [Comparative Example 2] A mixture of 23 g of CR-U (manufactured by Shin-Etsu Chemical Co., Ltd.) (as a non-volatile organic substance) and 202 g of octanol (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to 98 g of the precipitate obtained by the same method as in Example 1, and the mixture was dispersed using a homogenizer. 323 g of a composition containing 20% ​​by mass of cuprous oxide particles was obtained. The average particle size of the cuprous oxide particles was 26.2 nm, and the polydispersity index was 7.2%.

[0133] An attempt was made to form a dielectric on a polyimide substrate by the same procedure as in Example 1, but the dielectric was brittle and crumbled, making it impossible to measure the dielectric constant.

[0134] [Comparative Example 3] A composition (323 g) was obtained by the same procedure as in Example 5, except that the amount of hydrazine monohydrate added was 22 g. The cuprous oxide particles had an average particle size of 213 nm and a polydispersity index of 54.6%.

[0135] An attempt was made to form a dielectric on a polyimide substrate by the same procedure as in Example 1, but the dielectric cracked and the dielectric constant could not be measured. The results are shown in Table 1. [Table 1] [Industrial Applicability]

[0136] The dielectric material according to the present invention can be suitably applied to various electric components, particularly electromagnetic wave control elements. [Explanation of symbols]

[0137] 1. Laminate 11 Metal layer 12 Dielectric layer 13 Metal Pattern

Claims

1. A dielectric material comprising metal oxide particles and a non-volatile organic material, the metal oxide particles include copper oxide; The polydispersity index of the metal oxide particles is 10% or more and 40% or less, A dielectric, wherein a mass ratio of the metal oxide particles in the dielectric is 45 mass % or more and 95 mass % or less.

2. The dielectric according to claim 1 , wherein the dielectric constant of the dielectric is 1.5 or more and 10,000 or less.

3. The dielectric material according to claim 1 or 2, wherein the average particle size of the metal oxide particles is from 1 nm to 10 μm.

4. The dielectric material according to claim 1 or 2, wherein the non-volatile organic material has a relative dielectric constant of 2 or more and 30 or less.

5. A dielectric member comprising the dielectric according to claim 1 or 2, which is an insulating material for electronic devices, an insulating material for semiconductor elements, an inter-electrode material for capacitors, or an electromagnetic wave control material for electromagnetic wave control elements.

6. An electromagnetic wave control element including a dielectric layer made of the dielectric material according to claim 1 and a metal layer, An electromagnetic wave control element, wherein the dielectric layers are periodically arranged on the metal layer.

7. An electromagnetic wave control element including a dielectric layer made of a dielectric material and a metal layer, the dielectric layer comprises metal oxide particles and a non-volatile organic material; The polydispersity index of the metal oxide particles is 10% or more and 40% or less, The mass ratio of metal oxide particles in the dielectric is 45 mass% or more and 95 mass% or less, An electromagnetic wave control element, wherein the dielectric layers are periodically arranged on the metal layer.

8. Further comprising a periodically arranged metal pattern; The dielectric layer is present between the metal layer and the metal pattern.

8. The electromagnetic wave control element according to claim 6 or 7.

9. The area of ​​the metal layer is 100 mm 2 The electromagnetic wave control element according to claim 6 or 7.

10. 8. The electromagnetic wave control element according to claim 6, wherein the operating frequency is 0.7 GHz or more and 400 THz or less.

11. 11. The electromagnetic wave control element according to claim 10, which is an electromagnetic wave reflecting element having a reflection angle of 3° to 70° with respect to an electromagnetic wave incident at 0°.

12. 8. An electromagnetic wave transmitting / receiving system comprising: an electromagnetic wave control element according to claim 6 or 7; and an electromagnetic wave transmitting antenna.

13. A method for manufacturing an electromagnetic wave control element including a dielectric layer made of the dielectric material according to claim 1 and a metal layer, comprising the steps of: A method comprising printing a dielectric onto a metal layer to form said dielectric layer.

14. A method for manufacturing an electromagnetic wave control element including a dielectric layer made of a dielectric material and a metal layer, comprising the steps of: the dielectric layer comprises metal oxide particles and a non-volatile organic material; The polydispersity index of the metal oxide particles is 10% or more and 40% or less, The mass ratio of metal oxide particles in the dielectric is 45 mass% or more and 95 mass% or less, A method comprising printing a dielectric onto a metal layer to form said dielectric layer.

15. The electromagnetic wave control element further includes a metal pattern, 15. The method of claim 13 or 14, further comprising exposing the dielectric layer to energy radiation to form the metal pattern.

16. The method of claim 15 , wherein the energy irradiation is light irradiation.

Citation Information

Patent Citations

  • Radio wave absorber and production thereof

    JP1999204983A

  • Radio wave absorber and building material having radio wave absorption power

    JP2004119565A

  • Transparent dielectric film, capacitance type touch panel and flexible display

    JP2016216691A

  • Dielectric thin film

    JP2017145161A

  • Electromagnetic wave absorption sheet

    JP2022080991A